Soil moisture deficit induced changes in antioxidative defense mechanism of sugarcane (Saccharum officinarum) varieties differing in maturity - POOJA, POOJA; NANDWAL, A S; CHAND, MEHAR; PAL, AJAY; KUMARI, ANITA; RANI, BABITA; GOEL, VISHAL; KULSHRESHTHA, NEERAJ (The Indian Journal of Agricultural Sciences, 2020)
A split plot experiment was conducted at Regional Research Station, CCS HAU, Uchani, Karnal during 2014–15 and 2015–16 to investigate the effect of different soil moisture regimes on antioxidative defense mechanism of sugarcane (Saccharum officinarum L.) varieties. The experiment consisted of three moisture regimes based on available soil moisture i.e. irrigation at 50% ASM, 40% ASM and 30% ASM in main plot and four commercial sugarcane varieties, i.e. CoS 767, CoH 128, CoJ 64 and Co 0238 in sub plot with three replications. The observations recorded on antioxidative defense system have suggested possible key characteristics of drought tolerance. Low ASM levels induced the antioxidative defense system by increasing ROS and the specific activities of antioxidative enzymes, viz. peroxidase, catalase and ascorbate peroxidase. Specific activity of these enzymes increased in varieties Co 0238 and CoS 767 at 60 and 90 DAP. Severe stress of 30% ASM levels also resulted in a sharp rise in total ascorbic acid content (9.36 to 13.14 mg/g), total soluble proteins (from 9.6 to 13.77 mg/g), and the increase was more in varieties Co 0238 and CoS 767. A gradual decrease was observed in all the parameters after stress revival (120 DAP). ASM levels 30% and 40% significantly reduced K+ content in leaves (2.93 to 1.83%) as compared to 50% ASM level. So, it might be concluded from this study that biochemical traits had a significant varietal variation, indicating that these parameters could be used as screening criteria for selecting the tolerant and sensitive cultivars exposed to water limiting stress.